2014
DOI: 10.1093/ijnp/pyu006
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Effects of Abscisic Acid Mediated by the Downregulation of Corticotrophin-Releasing Hormone Gene Expression in Rats

Abstract: Background:Corticotrophin-releasing hormone (CRH) is considered to be the central driving force of the hypothalamic-pituitary-adrenal axis, which plays a key role in the stress response and depression. Clinical reports have suggested that excess retinoic acid (RA) is associated with depression. Abscisic acid (ABA) and RA are direct derivatives of carotenoids and share a similar molecular structure. Here, we proposed that ABA also plays a role in the regulation of CRH activity sharing with the RA signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Based on a series of pioneer studies, Zocchi's group demonstrated that ABA may act as an endogenous cytokine in inflammatory responses and stimulate the expansion of human mesenchymal stem cells in human granulocytes . In addition, ABA may also play a role in the stress response by downregulating the expression of the corticotrophin‐releasing hormone gene in rats . In addition, a possible role for ABA for cancer treatment was proposed more than three decades ago in an issued US patent .…”
mentioning
confidence: 99%
“…Based on a series of pioneer studies, Zocchi's group demonstrated that ABA may act as an endogenous cytokine in inflammatory responses and stimulate the expansion of human mesenchymal stem cells in human granulocytes . In addition, ABA may also play a role in the stress response by downregulating the expression of the corticotrophin‐releasing hormone gene in rats . In addition, a possible role for ABA for cancer treatment was proposed more than three decades ago in an issued US patent .…”
mentioning
confidence: 99%
“…The presence of ABA in the brain tissues of rats and pigs has been reported in 1986 ( Le Page-Degivry et al, 1986 ). It has been indicated that exogenous administration of ABA improves learning capability and mood state of rats ( Qi et al, 2014 , 2015 ; Naderi et al, 2017 ). So, it may be a potential therapeutic molecule of memory enhancer, which could be used in memory deficits disease, e.g., Alzheimer disease, in future study.…”
Section: Discussionmentioning
confidence: 99%
“…Although abscisic acid (ABA) and RA are direct derivatives of carotenoids and share a similar molecular structure (Bremner and McCaffery, 2008; Moise et al, 2009), recently we found a contrary role of ABA in regulating CRH expression compared with RA (Qi et al, 2015a). Under acute stress, ABA concentrations increased in the serum, but decreased in the hypothalamus and were accompanied by increased corticosterone in the serum and c-fos expression in the hypothalamus.…”
Section: Cis-elements and Transcription Factorsmentioning
confidence: 99%